Kesiagaan menghadapi bencana di Perpustakaan Kementerian “X” di Jakarta - Arnola Dewinta Hasan; Yeni Budi Rachman (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. This study aims to identify disaster preparedness conducted by the Library of the Ministry of